MEDIATIONG ROLE OF ORGANIZATIONAL COMMITMENT IN DEVELOPING EMPLOYEE PERFORMANCE- (STUDY IN REGIONAL SECRETARIAT OF BLORA REGION, CENTRAL JAVA, INDONESIA) - Estiningtyas, Evi Susiyanti; Darmanto, Susetyo (International Journal of Research -GRANTHAALAYAH, 2018)
The purpose of this study is to analyse the effect of locus of control and self-efficacy on the employee performance of Regional Secretariat of Blora Regency with organizational commitment as intervening variable. The data used is primary data by taking samples of employees in the Regional Secretariat of Blora Regency as many as 62 respondents. Path analysis with SPSS 22 statistical program is used for data analysis. Locus of control and self-efficacy had a positive and significant effect on organizational commitment. Self-efficacy also had positive effect on employed performance. Despite, Locus of control had negative effect on employee performance. Organizational commitment is also proven to have a mediating role, so it can be a factor that plays a role in encouraging employee performance improvement.